2009
DOI: 10.5688/aj730116
|View full text |Cite
|
Sign up to set email alerts
|

The Role and Education of the Veterinary Pharmacist

Abstract: Objective. To define the role and education of the traditional pharmacist who supports the needs of the veterinarian (hereafter referred to as veterinary pharmacist) and a pharmacist who practices solely in veterinary pharmacy (here after referred to as veterinary pharmacy specialist). Methods. The Delphi technique involving 7 panels of 143 experts was employed to reach consensus on the definition of the roles and education of the veterinary pharmacist and veterinary pharmacy specialist.Results. The veterinary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 15 publications
1
22
0
9
Order By: Relevance
“…[14][15][16][17][18][19] Developed by the Rand corporation in the 1950s, the Delphi was used as a qualitative, long-range forecasting technique 20 and method for improved decision making. 21 The Delphi process has been used in health professions education for identification of training needs 22 and competencies. [23][24][25] Powell argues that the success of a Delphi study rests on the expertise of the panel selected as participants.…”
Section: Methodsmentioning
confidence: 99%
“…[14][15][16][17][18][19] Developed by the Rand corporation in the 1950s, the Delphi was used as a qualitative, long-range forecasting technique 20 and method for improved decision making. 21 The Delphi process has been used in health professions education for identification of training needs 22 and competencies. [23][24][25] Powell argues that the success of a Delphi study rests on the expertise of the panel selected as participants.…”
Section: Methodsmentioning
confidence: 99%
“…Veterinary pharmacy services are increasing in the United States across all practice settings, and the knowledge and skills necessary to treat our animal patients may be another opportunity for academic and clinical partnerships. 65,66 It is incumbent on colleges/schools of pharmacy to continue to investigate emerging practice areas, as well as new opportunities within existing areas to better align and integrate with our clinical partners to lead the profession forward. Wellness and coaching are yet another group of areas that pharmacists may certify and earn credentials in; we must challenge student pharmacists in experiential settings to develop their prevention-and wellness-based education with patients as well.…”
Section: Strengthening the Value Proposition Of Experiential Educationmentioning
confidence: 99%
“…Ceresia et al found that while veterinarians and PharmDs with a knowledge of clinical, hospital, and community veterinary pharmacy reported that they think traditional pharmacists should be able to counsel pet clients almost to the extent as they would human patients, pharmacy academics lacked a consensus that nonspecialists need to be able to counsel clients on drug effects on animal pathophysiology, drug interactions, or adverse effects. 2 Academics also did not feel pharmacists needed to provide advice on differences in animal physiology, disease states, or administration techniques. Most nonacademic groups perceived a need for veterinary-related didactic course work in pharmacy school; academics at pharmacy schools however, did not.…”
Section: Introductionmentioning
confidence: 99%
“…However, pharmacists in these practices generally lack adequate training in veterinary medicine as it relates to therapeutics, [1][2][3] because most doctor of pharmacy (PharmD) curricula do not provide training in veterinary physiology, disease states, pharmacology, pharmacokinetics, drug administration, adverse effects, or disease or drug counseling. 4 Some pharmacists, therefore, can be uncomfortable with aspects of veterinary pharmacy such as specific companion animal disease states, pharmacotherapy options, dosages, informatics resources, and client counseling.…”
Section: Introductionmentioning
confidence: 99%